2012
DOI: 10.4238/2012.june.27.1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number variation and evolution in Neotropical Leguminoseae (Mimosoideae) from northeastern Brazil

Abstract: ABSTRACT. Most members of the subfamily Mimosoideae have pantropical distributions, variable habits, and a basic chromosome number x = 13. We examined karyotypic evolution of 27 species of this subfamily occurring principally in northeastern Brazil by examining chromosomes stained with Giemsa. All of the species had semireticulated interphase nuclei and early condensing segments in the proximal region of both chromosome arms. The basic number x = 13 was the most frequent, with 2n = 2x = 26 in 19 of the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…However, given that paleopolyploidy most likely occurred before the crown group divergence of Caesalpinioideae (Koenen et al, 2020b), and the fact that the mimosoid crown group diverged substantially later than that, paralog copies derived from this WGD are expected to have sufficiently divergent sequences across mimosoids for correct separation of paralogous sequences into separate alignments using the robust orthology assessment pipeline of Yang and Smith (2014) for most of these genes. Paleopolyploidy is also known to have occurred within the mimosoid clade (e.g., Leucaena , Govindarajulu et al, 2011; Mimosa , Dahmer et al, 2011), but chromosome count data suggest that these events were restricted to a few genera (Santos et al, 2012) and that polyploidy is most likely rare in the ingoid clade. Furthermore, this also suggests that a WGD event shared by a larger clade within mimosoids can probably be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that paleopolyploidy most likely occurred before the crown group divergence of Caesalpinioideae (Koenen et al, 2020b), and the fact that the mimosoid crown group diverged substantially later than that, paralog copies derived from this WGD are expected to have sufficiently divergent sequences across mimosoids for correct separation of paralogous sequences into separate alignments using the robust orthology assessment pipeline of Yang and Smith (2014) for most of these genes. Paleopolyploidy is also known to have occurred within the mimosoid clade (e.g., Leucaena , Govindarajulu et al, 2011; Mimosa , Dahmer et al, 2011), but chromosome count data suggest that these events were restricted to a few genera (Santos et al, 2012) and that polyploidy is most likely rare in the ingoid clade. Furthermore, this also suggests that a WGD event shared by a larger clade within mimosoids can probably be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…MacMill., and D. virgatus (L.) Willd., all counts are 2n = 28 (Turner & Beaman, 1953;Smith-White & al., 1963;Yeh & al., 1986;Kappali & Patil, 1987;. Santos & al. (2012) suggested a secondary basic number for the genus, x 2 = 14, possibly resulting from ascending dysploidy from the primary basic number, x 1 = 13.…”
Section: E49mentioning
confidence: 99%
“…This group is quite representative of caatinga, a biome exclusive to Brazil and characterized by semiarid climate, low average rainfall, rainfall seasonality, and strong endemism (Sampaio, 1995;Queiroz & al., 2009). This subfamily is little known cytologically, and chromosomal data for species endemic to, or occurring in, caatinga are incipient (Biondo & al., 2005;Santos & al., 2012). In this study, 7 of the 10 species analyzed corroborated literature data, while the numbers observed in Senna uniflora, Anadenanthera colubrina, and Piptadenia stipulacea are new records for these taxa.…”
Section: Literature Citedmentioning
confidence: 99%
See 2 more Smart Citations